2022
DOI: 10.12775/jehs.2022.12.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Diet and physical activity in the treatment of obesity - current knowledge

Abstract: Introduction: Obesity is now becoming a growing problem and challenge for medicine. The number of people with excessive body weight has now reached more than 2 billion, or about 30% of the world's population. The purpose of this article is to identify and describe some of the already known treatments for obesity, along with the latest research on the subject, in order to show the importance of developing and introducing new methods of weight loss.Aim of the study: The purpose of this article is to review the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In this context, exercise participation is particularly important. Research has shown that regular exercise participation not only helps individuals regulate their body weight and body fat percentage and prevent obesity ( Brzuszkiewicz et al, 2022 ; Gomes et al, 2023 ), but also has a positive impact on college students’ resilience ( Zach et al, 2021 ), emotional intelligence ( San Román-Mata et al, 2020 ) and mental health ( Ma et al, 2021 ). Despite the benefits of exercise participation to an individual’s physical and mental health, college students still face a number of challenges in adhering to exercise participation, including academic pressures, time constraints, and fewer available fitness classes ( Pellerine et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, exercise participation is particularly important. Research has shown that regular exercise participation not only helps individuals regulate their body weight and body fat percentage and prevent obesity ( Brzuszkiewicz et al, 2022 ; Gomes et al, 2023 ), but also has a positive impact on college students’ resilience ( Zach et al, 2021 ), emotional intelligence ( San Román-Mata et al, 2020 ) and mental health ( Ma et al, 2021 ). Despite the benefits of exercise participation to an individual’s physical and mental health, college students still face a number of challenges in adhering to exercise participation, including academic pressures, time constraints, and fewer available fitness classes ( Pellerine et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%